概念為本跨領域課程發展之研究—以國際文憑組織中學階段課程為例 Concept-Based Interdisciplinary Curriculum Development in International Baccalaureate Schools in Taiwan– The International Baccalaureate Middle Years Programme - 洪麗卿 Li-Ching Hung; 劉美慧 Meihui Liu; 王俐蘋 Li-Ping Wang (Journal of Research in Education Sciences)
本研究旨在借鏡國際文憑（International Baccalaureate, IB）學校概念為本跨領域課程發展模式，以提供國中階段統整課程發展之參考。本研究以二所臺灣實施中學階段課程（Middle Years Programme, MYP）學校進行個案研究，探究個案學校概念本位跨領域課程的發展歷程與轉化經驗。本研究藉由參與觀察、深入訪談和文件分析等方法蒐集資料，分析從內容為本轉向概念為本之跨領域課程發展模式。研究發現有五：一、跨領域課程發展歷程，以概念、探究通則為連貫要素，先進行單科內課程連結模式，再進行跨領域統整。二、教學活動採逆向式設計，並以探究任務具體勾勒出學習方向，藉此引導學生逐步主動建構出通則。三、IBMYP在教材和教法之彈性上提供國際文憑課程與國家課程調節的空間。四、各學科本身結構之強弱性質會影響概念為本跨領域課程發展之轉化情形。五、教師社群跨領域合作需要時間累進和經驗磨合，才能逐步跨越學科邊界。最後，綜合兩所學校實踐經驗，提供相關建議以供參考。 The International Baccalaureate Middle Years Programme (IBMYP) is based on an interdisciplinary educational framework distinct from the typically theme-based curriculum designs implemented in Taiwan, and it has been expanding rapidly in the Asia-Pacific region in recent years. Therefore, the case of the curriculum development for the IBMYP may provide valuable insights and potential directions for future curriculum development in Taiwan. Specifically, this explored how International Baccalaureate (IB) schools in Taiwan develop concept-based interdisciplinary curricula to thereby provide a reference for integrated curriculum development in junior high schools. This study investigated the development process and transformation experiences associated with the concept-based interdisciplinary curricula of the IBMYP in two case schools. The distinctive value of the two case schools, as explored in this study, lays in their implementation of the IB curriculum on a school-wide basis and across all grade levels (instead of as an additional program or in a limited number of experimental classes). Furthermore, the two schools differed in their developmental backgrounds and cultural contexts. One was a private secondary school that implemented the IBMYP curriculum and was predominantly staffed by expatriate teachers with IB teaching experience. The other was an IBMYP-certified public junior high school in Taiwan that implemented the IBMYP curriculum primarily through teachers with Taiwanese teacher certificates. This study explored the transition process from the traditional departmentalized public-school system to a concept-based interdisciplinary curriculum. Additionally, it examined the collaborative efforts of the teacher community in curriculum development and teaching practices, focusing on these two schools to provide valuable insights that were not based on a comparison of their relative merits. The research period spanned from January 2020 to December 2021. Multiple data collection methods, including document analysis, participant observation, and interviews, were applied. The findings of this study were as follows. (1) Concepts and generalization were regarded as the medium for integrating content during the interdisciplinary curriculum development process. For curriculum integration, the intradisciplinary-cohesion model was first adopted, followed by the interdisciplinary model. (2) Instructional activities were designed using a backward design approach, with inquiry-based tasks, multiple assessments, and rubrics clearly delineating learning objectives. These activities guided students in progressively and actively constructing principles. In class, implementing a student-centered inductive inquiry model instead of a teacher-centered deductive lecturing model was crucial. For educators accustomed to traditional objective-driven, lecture-style teaching, developing a concept-based curriculum necessitated a fundamental shift in their pedagogical mindset, prompting a transformative change in educational philosophy. (3) The current educational reform in Taiwan emphasizes inquiry-based learning and interdisciplinary curriculum design. However, specific guidance has not been provided regarding what this means for teaching practices. The conceptual framework, interdisciplinary integration, and diverse assessment principles of the IB curriculum design provided a reference that teachers could use to refine the curriculum reform process and operationalize the competency-oriented curriculum design of the new curriculum guidelines. The flexibility of the IBMYP in terms of its teaching materials and methods provided room for adjustments between the IB and Taiwanese education systems. These adjustments also promoted continual professional development and created reform momentum for teachers. (4) The development of concept-based interdisciplinary approaches varied across academic subjects because of differences in the systemic structures of their curriculum frameworks. For example, relative to the other subjects, Mathematics and Sciences underwent fewer adjustments in knowledge content. However, because the IBMYP curriculum emphasizes assessment performance and the “application” assessment dimension in both subjects, changes were still observed in how teachers assessed students’ ability to apply learned concepts in real-life contexts. (5) Regarding interdisciplinary collaboration within the teacher community, time and experience were required for disciplinary boundaries to be crossed. During the process of transforming the curriculum development model, which involved changes in curriculum content, teaching methods, and assessments, changes had to be achieved through collaborative discussions, consensus-building, and opinion integration within the teacher community. The current study synthesized empirical findings pertaining to two schools, revealing the strengths of each school. These findings suggest that the first school achieved a high level of horizontal integration across grades and effectively connected global and local experiences, serving as a model for future curriculum development. The second school conducted vertical integration over 3 years, focusing on coherence and alignment with the features of the National Curriculum Guideline 2019. This demonstrates the school’s pragmatic experiences in integrating the IB program into the national education system. The implications of this study were considered in combination with the practices of the two schools, and a concept-based interdisciplinary curriculum module was summarized to provide a reference for future implementation of such programs.